Molecular interactions of an alkaloid euchrestifoline as a new acetylcholinesterase inhibitor - Fazal Ur Rehman (Bangladesh Journal of Pharmacology, 2013)
Acetylcholinesterase (AChE) inhibitors are well established therapeutic agents for clinical management of Alzheimer's Diseases and other disorders associated with deficient cholinergic neurotransmission. In the current investigation, a new inhibitor has been reported for its significant AChE inhibitory. euchrestifoline was isolated from the extract of Murraya paniculata. Isolated compound showed significant enzyme inhibitory activity (IC50 value: 93.1 ± 0.0 ?M). Molecular docking revealed structural insights behind its significant inhibitory activity. Various molecular interaction were found between euchrestifoline and Ache especially Ser122, Trp84 and Tyr121. This study indicated promising potential of euchrestifoline to be further developed and explored as potential lead compound.